FSP1 is a glutathione-independent ferroptosis suppressor - Doll,S; Freitas,FP; Shah,R; Aldrovandi,M; da,Silva MC; Ingold,I; Grocin,AG; Xavier,da Silva TN; Panzilius,E; Scheel,CH; Mourão,A; Buday,K; et al. (Nature, 2019)
Ferroptosis is an iron-dependent form of necrotic cell death marked by oxidative damage to phospholipids1,2. To date, ferroptosis has been thought to be controlled only by the phospholipid hydroperoxide-reducing enzyme glutathione peroxidase 4 (GPX4)3,4 and radical-trapping antioxidants5,6. However, elucidation of the factors that underlie the sensitivity of a given cell type to ferroptosis7 is crucial to understand the pathophysiological role of ferroptosis and how it may be exploited for the treatment of cancer. Although metabolic constraints8 and phospholipid composition9,10 contribute to ferroptosis sensitivity, no cell-autonomous mechanisms have been identified that account for the resistance of cells to ferroptosis. Here we used an expression cloning approach to identify genes in human cancer cells that are able to complement the loss of GPX4. We found that the flavoprotein apoptosis-inducing factor mitochondria-associated 2 (AIFM2) is a previously unrecognized anti-ferroptotic gene. AIFM2, which we renamed ferroptosis suppressor protein 1 (FSP1) and which was initially described as a pro-apoptotic gene11, confers protection against ferroptosis elicited by GPX4 deletion. We further demonstrate that the suppression of ferroptosis by FSP1 is mediated by ubiquinone (also known as coenzyme Q10, CoQ10): the reduced form, ubiquinol, traps lipid peroxyl radicals that mediate lipid peroxidation, whereas FSP1 catalyses the regeneration of CoQ10 using NAD(P)H. Pharmacological targeting of FSP1 strongly synergizes with GPX4 inhibitors to trigger ferroptosis in a number of cancer entities. In conclusion, the FSP1-CoQ10-NAD(P)H pathway exists as a stand-alone parallel system, which co-operates with GPX4 and glutathione to suppress phospholipid peroxidation and ferroptosis.